Changes in defense capacity to infectious hematopoietic necrosis virus (IHNv) in rainbow trout intergenerationally exposed to glyphosate. Issue 122 (March 2022) - Le Du-Carrée, Jessy; Cabon, Joëlle; Louboutin, Lénaïg; Morin, Thierry; Danion, Morgane
Abstract: Glyphosate, the most widely used herbicide active substance worldwide, has raised many scientific, political and public debates in the context of its recent re-registration in the European Union, highlighting in particular a lack of data concerning its potential generational effects. In this study, we investigated the intergenerational toxicity of this active substance used alone or coformulated in glyphosate-based herbicides (GBHs) on the ability of rainbow trout ( Oncorhynchus mykiss ) to face a viral challenge. Juvenile trout from parents exposed for eight months to four different chemical exposure conditions (non-exposed control, pure glyphosate, Roundup Innovert®, and Viaglif Jardin® were experimentally infected with the infectious hematopoietic necrosis virus ( IHNv ). Various enzymatic and hemato-immunological markers were assessed before and after the viral challenge. Chemical contamination with GBHs strongly modulated viral trout susceptibility. Pure glyphosate induced a cumulative mortality of 35.8%, comparable to the control (37.0%), which was significantly reduced with Roundup Innovert® (−9.9%) and increased (+14.8%) with Viaglif Jardin®. No modification was observed for the biomarkers analysed for any conditions. These results demonstrate that the nature of the co-formulants associated to glyphosate in GHBs can modulate the susceptibility of fish to pathogens. Highlights: Intergenerationally glyphosate-exposed trout were infected to a virus. Contamination did not reveal profound physiological changes in juvenile trout. Pure glyphosate did not induce higher mortality but reduced interleukin-1 β . Glyphosate co-formulations modulated fish viral susceptibility. None of the studied hemato-immunological parameters explained differences in susceptibility.